2009
DOI: 10.1542/peds.2008-2635
|View full text |Cite
|
Sign up to set email alerts
|

Work of Breathing and Different Levels of Volume-Targeted Ventilation

Abstract: Addition of low VT levels to patient-triggered modes increases the WOB during weaning. This can be avoided by using a VT level of 6 mL/kg. ABSTRACTOBJECTIVES. The objectives of this study were to determine the impact of different volume-targeted levels on the work of breathing and to investigate whether a level that reduced the work of breathing below that experienced during ventilatory support without volume targeting could be determined.METHODS. The transdiaphragmatic pressure-time product, as an estimate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 17 publications
4
23
0
Order By: Relevance
“…A wide range of reported tidal volume (VT) levels (4-10 ml/kg) were used in the studies included in the meta-analysis [1]. We have shown that in the short-term, the work of breathing (WOB) is reduced during VTV if higher rather than lower levels of volume targeting are used [2,3,4]. Increasing the level of respiratory support by increasing the level of volume targeting, however, could unfavourably impact on respiratory muscle strength.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of reported tidal volume (VT) levels (4-10 ml/kg) were used in the studies included in the meta-analysis [1]. We have shown that in the short-term, the work of breathing (WOB) is reduced during VTV if higher rather than lower levels of volume targeting are used [2,3,4]. Increasing the level of respiratory support by increasing the level of volume targeting, however, could unfavourably impact on respiratory muscle strength.…”
Section: Introductionmentioning
confidence: 99%
“…The mean difference between settings of 30 min À1 and 50 min À1 was 6 min À1 (99% confidence interval [3][4][5][6][7][8][9]. No statistically significant differences were observed in delivered PIP or changes in TcCO 2 , FiO 2 , SpO 2 , HR or BP.…”
Section: Resultsmentioning
confidence: 86%
“…Synchronized intermittent mandatory ventilation provides a fixed number of triggered inflations per minute. AC has been associated with reduced patient effort 4,5 and reduced variability of tidal volume, 6 particularly when combined with volume guarantee (VG). 4,7 In AC mode, the ventilator rate varies with the breathing pattern of the infant.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we compared methods of weaning which supported all of the infant's breaths. We have previously reported that the work of breathing is increased during weaning when only a proportion of the infant's breaths were supported by mechanical inflations compared with when all the infant's breaths were supported 6. Our study has some limitations.…”
Section: Discussionmentioning
confidence: 85%
“…The work of breathing was assessed over a 5-min period on each occasion by measurement of the transdiaphragmatic pressure time product (PTPdi, New York, USA) as previously described in detail 6. The mean PTPdi was calculated from 20 consecutive infant's breaths including those that were or were not supported by positive pressure inflations.…”
Section: Introductionmentioning
confidence: 99%